Pengaruh Book-Tax Differences, Tingkat Utang, dan Perencanaan Pajak terhadap Persistensi Laba dengan Arus Kas Operasi sebagai Variabel Moderasi - Pratama, Sri Adi; Bawono, Andy Dwi Bayu (SEIKO : Journal of Management & Business, 2025)
This study aims to provide empirical evidence regarding the influence of book-tax differences, debt levels, and tax planning on profit persistence, as well as the role of operating cash flow in moderating the relationship between independent and dependent variables in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. This research employs a quantitative descriptive research design by conducting classical assumption tests, multiple linear regression analysis, and moderated regression analysis. The sampling method in this study employed purposive sampling, resulting in a sample of 108 data points used as research objects. The test results revealed that book-tax differences have a significant positive effect on profit persistence, while debt levels and tax planning have no significant effect on profit persistence. The moderated regression analysis results indicate that operating cash flow moderates the relationship between book-tax differences and profit persistence, but it does not moderate the relationships between debt levels and tax planning, respectively, and profit persistence.